Removal of toxic cadmium using a binary site ion‐exchange material derived from waste printed circuit boards. Issue 12 (14th September 2021) - Xu, Meng; Alyasi, Haya; Ning, Chao; Hui, Chi‐Wai; Mackey, Hamish; McKay, Gordon
Abstract: BACKGROUND: Adsorption has been widely applied in wastewater treatment for heavy metal removal. Due to the high cost of adsorbent materials, various types of materials including agricultural, industrial wastes and naturally abundant materials have emerged as low‐cost adsorbents in recent years. However, enhancement processes need to be developed to improve the adsorption capability of the raw materials. It is still a challenge to find an economic material with high adsorption capacity. This paper demonstrates a strategy to activate a recycled waste material using a simple activating process, while significantly improving the adsorption capacity of cadmium from wastewater. RESULTS: The raw material feedstock is the non‐metallic aluminosilicate material obtained from the recycling of waste printed circuit boards (PCBs). By a simple thermal alkali activation process using potassium hydroxide as activation agent, the product material shows a strong capability of cadmium removal from effluent containing a high adsorption capacity of 2.12 mmol g −1 . Initial metal concentration, dosage and pH effect on the adsorption isotherm and kinetics have been investigated. The experimental results include full characterization tests on this waste PCB‐derived adsorbent, and the in situ measurement of cadmium, calcium and potassium ions, since all are involved in the exchange sorption mechanism. CONCLUSION: By combining kinetic modelling analysis and X‐ray photoelectron spectroscopy, the novel adsorption mechanism has been explained and quantified as a dual ion‐exchange mechanism with the millimoles of cadmium exchanged mass balancing with the millimoles of calcium and 0.5 mmol potassium going into solution. © 2021 Society of Chemical Industry (SCI).